Urban–rural construction land transition and its coupling relationship with population flow in China's urban agglomeration region - Zhu, Congmou; Zhang, Xiaoling; Wang, Ke; Yuan, Shaofeng; Yang, Lixia; Skitmore, Martin (Cities, 2020)
Urban–rural construction land transition (URCLT) and population flow serve as two significant issues in the global process of urban–rural transition development. Better understanding of URCLT and its coupling relationship with population flow has great significance for enriching the theory of land use transitions and coordinating human–land dynamics in this process. This study develops a theoretical model of URCLT based on the land use transition theory using the structure transition index of urban-rural construction land (LUUR). In addition, a decoupling model is utilized to reveal the relationship between URCLT and rural-to-urban population flow. Taking the Yangtze River Delta Urban Agglomeration of China as an example, the results shows that LUUR in the study area experienced a rapid rise and then steady ascension during 2000–2015. The spatial transition trend of LUUR decreased as the distance from urban downtown increased and noticeably rose in the suburbs in the study period. The relationship between URCLT and rural-to-urban population flow converted from coupling in 2000–2005 to weak decoupling state during 2005–2015 and displayed substantial regional differences. Regulating URCLT and properly coordinating its relationship with population flow can help stabilize urban–rural transition development in China. •A theoretical model for the temporal and spatial transition of urban-rural construction land is developed.•A structure transition index at grid scale was employed to analyze the temporal and spatial transition characteristics of urban-rural construction land.•A decoupling model was used to reveal the relationship between urban-rural construction land transition and rural-to-urban population flow.